(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
Hyperbole is a figure of speech and literary device that creates heightened effect through deliberate exaggeration. Hyperbole is often a boldly overstated or exaggerated claim or statement that adds emphasis without the intention of being literally true. In rhetoric and literature, hyperbole is often used for serious, comic, or ironic effects. A hyperbole is a literary device wherein the author uses specific words and phrases that exaggerate and overemphasize the basic crux of the statement in order to produce a grander, more noticeable effect. The purpose of hyperbole is to create a larger-than-life effect and overly stress a specific point. Such sentences usually convey an action or sentiment that is generally not practically realistically possible or plausible but helps emphasize an emotion. In this article we can also discuss about hyperbole as a stylistic device